Population differentiation for germination and early seedling root growth traits under saline conditions in the annual legume Medicago truncatula (Fabaceae)1. Issue 3 (1st March 2014) - Cordeiro, Matilde A.; Moriuchi, Ken S.; Fotinos, Tonya D.; Miller, Kelsey E.; Nuzhdin, Sergey V.; von Wettberg, Eric J.; Cook, Douglas R.
Abstract : Premise of the study: Seedling establishment and survival are highly sensitive to soil salinity and plants that evolved in saline environments are likely to express traits that increase fitness in those environments. Such traits are of ecological interest and they may have practical value for improving salt tolerance in cultivated species. We examined responses to soil salinity and tested potential mechanisms of salt tolerance in Medicago truncatula, using genotypes that originated from natural populations occurring on saline and nonsaline soils. Methods: Germination and seedling responses were quantified and compared between saline and nonsaline origin genotypes. Germination treatments included a range of sodium chloride (NaCl) concentrations in both offspring and parental environments. Seedling treatments included NaCl, abscisic acid (ABA), and potassium chloride (KCl). Key results: Saline origin genotypes displayed greater salinity tolerance for germination and seedling traits relative to nonsaline origin genotypes. We observed population specific differences for the effects of salinity on time to germination and for the impact of parental environment on germination rates. ABA and NaCl treatments had similar negative effects on root growth, although relative sensitivities differed, with saline population less sensitive to NaCl and more sensitive to ABA compared to their nonsaline counterparts. Conclusions: We report population differentiation for germination and seedling growth traits under saline conditions among populations derived from saline and nonsaline environments. These observations are consistent with a syndrome of adaptations for salinity tolerance during early plant development, including traits that are common among saline environments and those that are idiosyncratic to local populations.